Transceive phase corrected 2D contrast source inversion‐electrical properties tomography. Issue 5 (6th December 2020) - Stijnman, Peter R. S.; Stefano Mandija,; Fuchs, Patrick S.; van den Berg, Cornelis A. T.; Remis, Rob F.
Abstract : Purpose: To remove the necessity of the tranceive phase assumption for CSI‐EPT and show electrical properties maps reconstructed from measured data obtained using a standard 3T birdcage body coil setup. Methods: The existing CSI‐EPT algorithm is reformulated to use the transceive phase rather than relying on the transceive phase assumption. Furthermore, the radio frequency (RF)‐shield is numerically implemented to accurately model the RF fields inside the MRI scanner. We verify that the reformulated two‐dimensional (2D) CSI‐EPT algorithm can reconstruct electrical properties maps given 2D electromagnetic simulations. Afterward, the algorithm is tested with three‐dimensional (3D) FDTD simulations to investigate if the 2D CSI‐EPT can retrieve the electrical properties for 3D RF fields. Finally, an MR experiment at 3T with a phantom is performed. Results: From the results of the 2D simulations, it is seen that CSI‐EPT can reconstruct the electrical properties using MRI accessible quantities. For 3D simulations, it is observed that the electrical properties are underestimated, nonetheless, CSI‐EPT has a lower standard deviation than the standard Helmholtz based methods. Finally, the first CSI‐EPT reconstructions based on measured data are presented showing comparable accuracy and precision to reconstructions based on simulated data, and demonstrating the feasibility of CSI‐EPT. Conclusions: The CSI‐EPT algorithm was rewritten to use MRI accessible quantities. This allows for CSI‐EPT to fully exploit the benefits of the higher static magnetic field strengths with a standard quadrature birdcage coil setup.